To study the mechanism of Scutellariae Radix and Astragaloside in the treatment of lung cancer based on network pharmacology. Issue 26 (30th June 2022) - Wang, Zijuan; Meng, Lingpeng; Shan, Jingyi; Pei, Liangyu; Bao, Leri; Li, Xi; Lin, Yudong; Gu, Xian; Xu, Zhenye
Abstract : The aim of the study wasto explore the target and potential mechanism of Scutellariae Radix and Astragaloside in the treatment of lung cancer infection by network pharmacology. The target information of baicalein and flavonin was mined from CTD database and Swiss database. Genecards database, DRUGBANK database, and OMIM database were used to search for lung cancer related genes. The target protein network map (PPI) was drawn by using the STRING database analysis and Cytoscape3.7.1 software. With the help of Perl language, the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis and gene function analysis (GO) enrichment analysis were carried out by using the biological program package of R language. In total, 347 biological targets of Astragaloside and Scutellariae Radix were identified through the collection and analysis of multiple databases. In total, 1526 lung cancer targets were obtained from a multi-disease database. The "component-target" network of Astragaloside and Scutellariae Radix was constructed, and the protein interaction network (PPI) of the overlapping targets was analyzed to identify the key targets of drug-influenced diseases. In addition, KEGG pathway analysis and GO enrichment analysis were performed on the overlapping targets to explore the mechanism of Scutellariae Radix and Astragaloside in the treatment of lung cancer. Scutellariae Radix and Astragaloside have the characteristics of multi-component, multi-target and multi-pathway in the treatment of lung cancer, which provides a new idea and scientific basis for further research on the molecular mechanism of the antilung cancer effect of Scutellariae Radix and Astragaloside.